Organic crystal coating method and method for improving terahertz wave emission efficiency of organic nonlinear crystal

By plating CYTOP film on the surface of organic nonlinear crystals, and reducing light reflection using amphipathic film technology, the problem of optical reflection loss of organic crystals in terahertz wave emission is solved, the terahertz wave emission efficiency is achieved, and the long-term stability protection of the crystal is provided.

CN119869883APending Publication Date: 2025-04-25QINGDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510044764.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Organic nonlinear crystals have significant optical reflection loss in terahertz wave emission, resulting in low emission efficiency, limiting their application in biomedical engineering, non-destructive testing and other fields.

Method used

By plating a thin film of liquid polymer CYTOP on the surface of the organic crystal, the induced-transmissive film technology reduces the reflection of light and increases the transmittance of light, thereby improving the emission efficiency of terahertz waves.

Benefits of technology

Compared with uncoated crystals, the time domain enhancement efficiency of the terahertz emission signal of the organic crystal after coating is increased by at least 16.7%, and the frequency domain enhancement efficiency is increased by at least 16.5%. At the same time, the crystal after coating is stored stably in the air for at least 1 year to prevent delivery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869883A_ABST
    Figure CN119869883A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of application of film functional materials, and relates to a film coating method of an organic crystal and a method for improving terahertz wave emission efficiency of an organic nonlinear crystal. According to the method, the two surfaces of the organic crystal can be plated with antireflection films, Fresnel reflection loss generated on the surface of the organic crystal by incident light in the optical application process of the organic crystal is reduced, and the effect of improving the terahertz emission efficiency by antireflection of the incident light in the organic crystal is achieved; meanwhile, the purposes of protecting the organic crystal material and preventing deliquescence can be achieved. A thin film material CYTOP is selected, firstly, the thickness of the antireflection film to be plated is calculated according to the light propagation theory, the rotating speed of a spin coater and the spin coating duration are controlled through a spin coating method, the drying time is accurately controlled, and the antireflection film is formed on the surface of the organic nonlinear crystal. Compared with an uncoated crystal, the terahertz emission signal time domain enhancement efficiency is at least improved by 16.7%, the terahertz emission signal frequency domain enhancement efficiency is at least improved by 16.5%, and the coated crystal can be stably stored in air for at least one year.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of application of functional materials, and relates to a coating method for an organic crystal and a method for improving the terahertz wave emission efficiency of an organic nonlinear crystal, specifically a method for reducing the optical reflection loss of an organic crystal, improving the terahertz wave emission efficiency and realizing crystal protection. Background Art

[0002] Terahertz (THz) has been widely used in various fields such as biomedical engineering, nondestructive testing, high-speed communication and ultrafast spectroscopy due to its characteristics of penetration, safety and wide spectrum. Organic nonlinear optical crystals have great potential in the application of terahertz emission sources due to their high nonlinear coefficient, small dielectric constant and large electro-optic coefficient.

[0003] In recent years, researchers have gradually improved the power and spectral width of terahertz emission through material modification and crystal growth optimization. Among them, material modification can change the nonlinear optical properties of the original crystal by doping the original crystal or designing the molecular structure, thereby achieving the purpose of improving the terahertz emission efficiency. Crystal growth optimization is to control the crystal growth conditions to grow an ideal crystal with few defects and excellent morphology, and by selecting a suitable crystal orientation, the nonlinear optical effect can be enhanced, thereby improving the efficiency of THz emission. However, the material modification method changes the structure of the original crystal, and this method may not significantly improve the terahertz performance of some typical crystals. For example, the terahertz performance of DSTMS and DCSC crystals redesigned on the basis of DAST is not as good as DAST. This method of crystal growth optimization does not change the original properties of the crystal, but it takes a long time and is difficult to grow a crystal with few defects and a shape that meets the test conditions. In the prior art, CN103757706A discloses a method for preparing a nonlinear optical crystal surface anti-reflection protective film, and CN111636099A discloses a method for preventing nonlinear crystal desiccants, which effectively prevents the crystal from moisture by coating. However, the intensity of terahertz waves generated by organic nonlinear crystals is proportional to the square of the incident intensity of the excitation light. However, the Fresnel reflection loss of the excitation light on the crystal surface is very significant. When the pump laser is incident on the crystal surface, a large proportion of the pump power is reflected and lost from the air-crystal interface, resulting in the emission efficiency of terahertz emission sources based on organic crystals always remaining at a low level, greatly limiting the application prospects of organic crystals as terahertz wave emission sources. The terahertz reflection loss on the surface of organic crystals is a key issue that needs to be urgently addressed. Summary of the invention

[0004] In view of the above problems, the purpose of the present invention is to provide a method for coating an organic crystal and a method for improving the terahertz wave emission efficiency of an organic nonlinear crystal, which can not only reduce the optical reflection loss of the organic nonlinear crystal and improve the terahertz wave emission efficiency, but also protect the crystal material from absorbing water vapor in the air and causing deliquescence, which makes it unusable.

[0005] To achieve the above object, the present invention provides a method for coating an organic crystal, comprising the following specific steps:

[0006] (1) First, select an organic crystal with a smooth surface, place it at the center of the turntable of a spin coating instrument and fix it;

[0007] (2) Using liquid polymer CYTOP as the coating material, the reflectivity R of the coated crystal to the incident light and the reflectivity r of the uncoated crystal to the incident light are calculated using the light propagation theory formulas (1) and (2).

[0008]

[0009] where n air is the refractive index of air, n crystal is the refractive index of the organic crystal, n film is the refractive index of CYTOP, R is the reflectivity of the crystal to the incident light after coating, and r is the reflectivity of the uncoated crystal to the incident light;

[0010] (3) When the spin coating apparatus is stationary, use a 0.1 ml dropper to drop a drop of CYTOP solution in the middle of the crystal; control the spin coating machine turntable speed to 500-900 rpm / min, and the spin coating time to 20-50 seconds; after the coating is completed, the coating solution is evenly coated on the surface of the organic crystal;

[0011] (4) The organic crystal is allowed to stand for 10 minutes to initially air-dry the coating solution, and then transferred to a vacuum drying oven to dry the coating solution at 50° C. for 30 minutes to form a stable film on the surface of the crystal;

[0012] (5) Repeat steps (3) and (4) to form a double-sided coating process to obtain a coated crystal.

[0013] The present invention also provides a coated organic crystal obtained by the above method, and application of the method in improving the terahertz wave emission efficiency of an organic nonlinear crystal.

[0014] The present invention further provides a method for improving the terahertz wave emission efficiency of an organic nonlinear crystal. The coated crystal obtained by the above method is placed at the emission source of a terahertz time-domain spectroscopy system, and a pump laser with a wavelength of 1560 nm is irradiated to the center of the crystal surface. The time-domain waveform of the terahertz wave emission wave is recorded. The terahertz time-domain amplitudes of the coated and uncoated crystals are respectively recorded as f(t1) and f(t2). The time-domain enhancement efficiency of the terahertz emission signal is calculated by formula (3). The time-domain waveform data of the terahertz emission wave is imported into OriginLab software. The frequency-domain spectrum corresponding to the terahertz time-domain waveform is obtained by fast Fourier transform instruction operation (signal processing---FFT). The terahertz frequency-domain spectra of the coated and uncoated crystals are respectively recorded as T(ω1) and T(ω2). The frequency-domain enhancement efficiency of the terahertz emission signal is calculated by formula (4).

[0015]

[0016] The method of the present invention can reduce the optical loss of organic crystals and improve the emission of terahertz wave signals. Compared with uncoated crystals, the time domain enhancement efficiency of terahertz emission signals is increased by at least 16.7%, and the frequency domain enhancement efficiency of terahertz emission signals is increased by at least 16.5%. The coated crystals can be stably stored in the air for at least one year.

[0017] In the present invention, the inventors first proposed a method for improving the terahertz emission efficiency through thin film technology, starting from the surface of the crystal using thin films to increase the interaction area between light and materials, thereby improving the terahertz conversion efficiency. This method not only does not change the structural properties of the crystal itself, but also has a much higher efficiency than growing high-quality crystals. In particular, the inventors applied this method to organic crystals and proposed a method that can prevent Fresnel reflection loss of lasers on the surface of organic crystals, which can further enhance the intensity of terahertz waves generated in organic crystals and improve the terahertz wave emission efficiency of organic crystals.

[0018] In the method described in the present invention, the anti-reflection film technology plays a key role. The interference of light is controlled by accurately calculating the thickness of different anti-reflection films. Therefore, the coating technology is very demanding and directly affects the application effect after coating. In particular, in view of the particularity of organic crystals, the present invention preferably coats the film by a spin coating method. This method not only avoids the use of high temperature operating environments and chemical reagents in vacuum evaporation, sputtering coating or chemical vapor deposition (CVD), but also overcomes the problem that the coating effect is difficult to control in relatively mild processes such as spraying, dripping or dipping, and can also obtain a thinner and controllable coating by correcting the rotation speed. The organic crystal with a smooth surface described in the present invention refers to an organic crystal with a surface roughness of less than 1 micron to prevent uneven surface coating. The inventors have found through testing that the amount of the coating solution has nothing to do with the thickness of the coating, and the adhesion between the coating solution of different concentrations and the crystal is different, which affects the control of the coating thickness; the spin coating time and the spin coating turntable speed both affect the coating thickness, and it is necessary to reasonably control the spin coating machine turntable speed and spin coating time parameters.

[0019] Similarly, the anti-reflection coating technology also has high requirements for coating materials, which should have low loss in the terahertz band and visible light band, good insulation and hydrophobicity with organic materials, etc. Therefore, in the selection of coating materials, the inventors first selected CYTOP as the coating material for organic crystals. CYTOP is a liquid polymer with a transparency of up to 99% in the terahertz band and a refractive index of 1.03. In addition, its refractive index n is 1.03 in the 1560 nanometer band. film =1.3, which meets the requirements of the present invention; in addition, the water absorption rate of CYTOP is less than 0.01%, which can play a moisture-proof effect on ionic organic nonlinear optical crystals.

[0020] In the present invention, the theoretical optical medium thickness d=300 nm of the CYTOP film is calculated according to formula (1); CYTOP is dissolved in a resin solvent to obtain a CYTOP solution, wherein the solvent is decafluoro-3-methoxy-2-(trifluoromethyl)pentane; the mass percentage of CYTOP and the solvent in the CYTOP solution is 1%-10%, preferably 1-3%, and more preferably 1%; the spin coating speed is 500-900 rpm / min, preferably 700-900 rpm / min, and more preferably 900 rpm / min; and the spin coating time is 20-50 s, and more preferably 30 s.

[0021] The present invention adopts a double-sided coating process to obtain a coated crystal, forming two interfaces of air-film and film-crystal. When a laser beam irradiates the crystal, the laser will generate two reflected waves at the two interfaces. When the two reflected waves have the same intensity and a phase difference of π, due to the effect of optical interference, the total energy of the reflected waves is zero, thereby improving the laser transmittance (i.e., the transmitted laser intensity), and the terahertz wave emission signal is proportional to the transmitted laser intensity. Therefore, the terahertz wave emission efficiency of organic crystals will be improved.

[0022] Compared with the prior art, the present invention applies the working principle of anti-reflection film, and by coating a thin film on the surface of the optical element, the phase of the reflected light can be changed. The anti-reflection film can make the phase difference between the reflected light and the transmitted light exactly half the wavelength (180°), causing the reflected light to interfere with each other, reducing the intensity of the reflected light, thereby increasing the transmittance and improving the terahertz emission efficiency. The inventors also unexpectedly discovered that the anti-reflection film technology can not only improve the efficiency of the crystal terahertz wave generation, but also protect the crystal from deliquescence. Compared with uncoated crystals, the present invention increases the time domain enhancement efficiency and frequency domain enhancement efficiency of the terahertz wave emission signal of the DAST crystal by at least 16%. The uncoated DAST is stored in the air for less than one month due to water absorption and deliquescence. After coating, the crystal can be stably stored in the air for at least 1 year. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The schematic diagram is a principle diagram of the method of the present invention.

[0024] Figure 2 For CYTOP TM Molecular structure of (produced by AGC Chemical Co., Ltd.)

[0025] Figure 3 The surface morphology of DAST organic crystal before and after anti-reflection coating. (a) is the surface morphology of DAST before coating, (b) is the surface morphology of DAST after coating, and (c) is the microscope image of the anti-reflection coating.

[0026] Figure 4 Comparison of the (a) time domain waveform and (b) frequency domain spectrum of the terahertz emission of the DAST crystal before and after anti-reflection coating.

[0027] Figure 5 A comparison of the deliquescence of DAST coated with an anti-reflection coating (left) and DAST without a coating (right) after being placed in the air for one year. DETAILED DESCRIPTION

[0028] Example 1

[0029] This embodiment provides a DAST (methylpyridine toluene sulfonate) organic crystal coating method and the coated organic crystal obtained by the method. The coating method includes the following specific steps:

[0030] (1) Select two organic nonlinear crystals DAST with smooth surfaces (roughness < 0.1 μm) and no obvious defects, place them at the center of the turntable of the spin coating instrument and fix them;

[0031] (2) For organic crystal DAST (n crystal =2.1, λ=1560nm), CYTOP is used as the coating material, and its molecular structure is as follows Figure 2 , CYTOP at λ = 1560nm film =1.3, calculate the thickness of the antireflection film

[0032] (3) According to the light propagation theory formulas (1) and (2), the reflectivity of the incident light on the surface of the DAST crystal with a coating thickness of 300 nm is R = 16%, and the reflectivity of the uncoated DAST crystal to the incident light is r = 35%. Theoretical calculation and analysis show that the anti-reflection coating will reduce the reflectivity of the incident light to rR = 19%;

[0033]

[0034] where n air is the refractive index of air, n crystal is the refractive index of the organic crystal, n film is the refractive index of CYTOP, R is the reflectivity of the crystal to the incident light after coating, and r is the reflectivity of the uncoated crystal to the incident light;

[0035] (4) Dissolving CYTOP (CTL-109AC, manufacturer: AGC chemical Inc.) in a resin solvent, wherein the solvent is decafluoro-3-methoxy-2-(trifluoromethyl)pentane, also known as 3-methoxyperfluoro(2-methylpentane); preparing CYTOP coating solutions with a mass percentage of CYTOP to solvent of 1%, 3%, 5%, 7%, and 9%, respectively; dropping a drop of the coating solution onto the center of the DAST crystal using a 0.1 ml dropper while the spin coating apparatus is stationary;

[0036] Select a coating solution with a CYTOP and solvent mass percentage of 1%, fix the spin coating time to 30s, and the relationship between the spin coating speed and the coating thickness is shown in Table 1; select a coating solution with a CYTOP and solvent mass percentage of 1%, and fix the spin coating speed to 900rpm / min, and the relationship between the spin coating time and the coating thickness is shown in Table 2; In order to obtain a 300nm thick coating effect, for different solution concentrations, at a fixed speed of 900rpm / min, the required coating time is shown in Table 3;

[0037] Table 1 Relationship between spin coating speed and film thickness

[0038] CYTOP and solvent mass percentage Speed ​​(rpm / min) Film thickness (nm)(±5%) Time(s) 1% 100 <![CDATA[2*10 4 ]]> 30 1% 300 5000 30 1% 500 1500 30 1% 700 900 30 1% 900 300 30

[0039] Table 2 Relationship between spin coating time and film thickness:

[0040] CYTOP and solvent mass percentage Speed ​​(rpm / min) Film thickness (nm)(±5%) Time(s) 1% 900 2100 5 1% 900 1200 10 1% 900 850 15 1% 900 600 20 1% 900 400 25 1% 900 300 30 1% 900 250 35

[0041] Table 3 Relationship between CYTOP concentration and process time of 300nm film:

[0042] CYTOP and solvent mass percentage Speed ​​(rpm / min) Film thickness (nm)(±5%) Time(s) 1% 900 300 30 3% 900 300 35 5% 900 300 38 7% 900 300 41 9% 900 300 45

[0043] (5) After the spin coating is completed, the DAST crystal is allowed to stand for ten minutes to initially air dry the coated film, and then placed in a vacuum drying oven at 50°C to dry the coating solution for 30 minutes to form a stable film on the crystal surface; Figure 3 (a) is the uncoated DAST crystal. Figure 3 (b) is the DAST crystal after coating. Figure 3 (c) is the film thickness observed by scanning electron microscopy, which is about 301.3 nm, which is generally in line with the experimental calculation requirements;

[0044] (6) Take out the dried crystal and repeat steps (4) and (5) to complete double-sided coating to obtain a coated crystal.

[0045] Example 2

[0046] This embodiment provides a method for improving the terahertz wave emission efficiency of DAST (methylpyridine toluene sulfonate) organic crystals. The coated crystal and the uncoated crystal obtained in Example 1 are respectively used as terahertz wave emission sources, and are respectively placed at the "emitter" emission source of a terahertz time-domain spectroscopy system, such as Qingdao Qingyuan Fengda QT-TRS1000 terahertz time-domain spectroscopy teaching and research system, so that the pump laser (wavelength 1560nm) is irradiated to the center of the crystal surface, and the time domain waveform of the terahertz wave emission wave is recorded, such as Figure 4 (a), the terahertz time domain amplitudes of the coated and uncoated crystals are recorded as f(t1) and f(t2), respectively. The time domain enhancement efficiency of the terahertz emission signal is calculated by formula (3), A = (0.0006-0.0005) / 0.0006*100% = 16.7%;

[0047]

[0048] The terahertz wave emission time domain waveform data is imported into the OriginLab software, and the frequency domain spectrum corresponding to the terahertz time domain waveform is obtained through the fast Fourier transform instruction operation (signal processing---FFT), such as Figure 4(b), the terahertz frequency domain spectra of the coated and uncoated crystals are denoted as T(ω1) and T(ω2), respectively. The frequency domain enhancement efficiency of the terahertz emission signal is calculated by formula (4), B = (-79 + 92) / 79 * 100% = 16.5%.

[0049]

[0050] The coated crystals and uncoated crystals obtained in Example 1 were placed in the air to observe their deliquescence. The observation period was 1 year, and the protective effect of the coating was compared and tested. Figure 5 The left side shows the morphology of the uncoated crystal after one year. It can be seen that the surface of the crystal is green, which is a change in properties caused by the crystal absorbing water and deliquescing; Figure 5 The right side shows the morphology of the crystal after coating for one year. It can be seen that the crystal still appears orange-red and has good optical transmittance. This proves that the coating treatment has a good protective effect on the long-term stable terahertz source emission of the crystal.

Claims

1. A method for coating an organic crystal, characterized in that: The specific steps include: (1) First, select an organic crystal with a smooth surface, place it at the center of the turntable of a spin coating instrument and fix it; (2) Using liquid polymer CYTOP as the coating material, the reflectivity of the coated crystal to the incident light and the reflectivity of the uncoated crystal to the incident light are calculated using the light propagation theory; (3) Drop a drop of CYTOP solution in the middle of the crystal while the spin coating instrument is stationary; control the rotation speed of the spin coating instrument turntable to 500-900 rpm / min, and the spin coating time to 20-50 seconds; after the coating is completed, the CYTOP solution is evenly coated on the surface of the organic crystal; (4) leaving the organic crystal to stand for a period of time to initially air-dry the coating solution, and then transferring it to a vacuum drying oven to dry it, so as to form a stable film on the surface of the crystal; (5) Repeat steps (3) and (4) to form a double-sided coating process to obtain a coated organic crystal.

2. The method for coating an organic crystal according to claim 1, characterized in that: The organic crystal with a smooth surface refers to an organic crystal with a surface roughness less than 1 micron.

3. The method for coating an organic crystal according to claim 1, characterized in that: The light propagation theory calculates the reflectivity R of the coated crystal to the incident light and the reflectivity r of the uncoated crystal to the incident light according to formulas (1) and (2). Where n air is the refractive index of air, n crystal is the refractive index of the organic crystal, n film is the refractive index of CYTOP, R is the reflectivity of the crystal to the incident light after coating, and r is the reflectivity of the uncoated crystal to the incident light.

4. The method for coating an organic crystal according to claim 1, characterized in that: CYTOP is a liquid polymer with a transparency of up to 99% in the terahertz band and a refractive index of 1.

03. film =1.3, calculate the thickness of the antireflection film The water absorption of CYTOP is less than 0.01%.

5. The method for coating an organic crystal according to claim 1, characterized in that: CYTOP is dissolved in a resin solvent to obtain a CYTOP solution, wherein the resin solvent is decafluoro-3-methoxy-2-(trifluoromethyl)pentane.

6. The method for coating an organic crystal according to claim 1, characterized in that: The mass percentage of CYTOP to solvent in the CYTOP solution was 1%, the spin coating speed was 900 rpm / min, and the spin coating time was 30 s.

7. The method for coating an organic crystal according to claim 1, characterized in that: In step (3), a drop of CYTOP solution is dropped into the center of the crystal using a 0.1 ml dropper; in step (4), the organic crystal is allowed to stand for 10 minutes to initially air-dry the coating solution, and then transferred to a vacuum drying oven to dry the coating solution at 50° C. for 30 minutes.

8. Application of the method according to any one of claims 1 to 7 in improving the terahertz wave emission efficiency of organic nonlinear crystals.

9. A method for improving the terahertz wave emission efficiency of an organic nonlinear crystal, characterized in that: The coated crystal obtained by the method described in any one of claims 1 to 7 is placed at the emission source of the terahertz time-domain spectroscopy system, and a pump laser with a wavelength of 1560 nm is irradiated to the center of the crystal surface. The time domain waveform of the terahertz wave emission wave is recorded, and the terahertz time domain amplitudes of the coated and uncoated crystals are respectively recorded as f(t1) and f(t2), and the time domain enhancement efficiency A of the terahertz emission signal is calculated by formula (3); the time domain waveform data of the terahertz wave emission wave is imported into the OriginLab software, and the frequency domain spectrum corresponding to the terahertz time domain waveform is obtained by the fast Fourier transform instruction operation. The terahertz frequency domain spectra of the coated and uncoated crystals are respectively recorded as T(ω1) and T(ω2), and the frequency domain enhancement efficiency B of the terahertz emission signal is calculated by formula (4).

10. The method for improving the terahertz wave emission efficiency of an organic nonlinear crystal according to claim 9, characterized in that: Compared with uncoated crystals, the time domain enhancement efficiency of terahertz emission signals is increased by at least 16.7%, and the frequency domain enhancement efficiency of terahertz emission signals is increased by at least 16.5%. The coated crystals can be stably stored in the air for at least 1 year.

Citation Information

Patent Citations

  • Preparation method of nonlinear optical crystal surface antireflection protective film

    CN103757706A

  • Method for preventing moisture degradation of nonlinear crystal

    CN111636099A